Material Specifications for the Production of High-Density Refractory Brick with Locally Available High Alumino Silicates (Journal of Science and Technology, 2016)
An attempt was made to select refractory alumino-silicates and high alumina bearing minerals available in the country to develop dense refractory bricks for the metallurgical industries. Selective properties such as chemical analysis, mineralogy, % apparent porosity, cold crushing strength, pyrometric cone equivalent (P.C.E) were looked at with the view of finding out the best material for the development of dense refractories.Awaso bauxite and Cape Coast clay were selected. Material specification, processing requirement, production and testing methods were reviewed. Cape Coast clay was successfully bench marked against known fireclays. The results obtained from the use of Awaso bauxite revealed that though Awaso bauxite has high alumina content the bricks produced from it suffer very high re-heating shrinkage indicating low mineral stability in the grog. However, Cape Coast clay based bricks at 1350°C were found to have adequate properties with mullite crystalline phase which is decisive for high temperature behavior of the bricks – a guarantee in service conditions and very comparable to the properties of refractory bricks from the U.K. Finally it was established that the higher the % apparent porosity the higher the re-heating shrinkage of the bricks produced from such compositions.